Female Islamic Scholars in the Digital Space: Transformations, Challenges, and Contributions - Nasri, Ulyan; Rahmatullah, Abdul Malik Salim (Digital Muslim Review, 2024)
This paper examines the presence of female scholars in digital spaces, with a focus on their roles, contributions, and the challenges they face. Employing a qualitative method- ology, the study utilises data collection techniques such as a literature review of scholarly articles and relevant online sources. The digital data examined in this research comprises scholarly articles and pertinent online resources. The data analysis employs thematic anal- ysis to identify patterns and key themes, providing a deeper understanding of the phe- nomenon under investigation. The findings reveal that female scholars, such as Ustadzah Halimah Alaydrus, Ning Imaz Fatimatuz Zahra, and Umi Lailatul Rahma Adi, play a piv- otal role in shaping religious discourse in the digital realm. However, they face numerous challenges, including online harassment and gender discrimination. The implications of this study emphasise the necessity of fostering inclusive digital environments that support the full participation of women on various online platforms. Additionally, the research ad- vocates for continued investigation and dialogue to advance gender equality within Islamic scholarship and to promote inclusive approaches to Islamic thought in the digital age.